2013
DOI: 10.1371/journal.pone.0076499
|View full text |Cite
|
Sign up to set email alerts
|

Misuse and Dependence on Non-Prescription Codeine Analgesics or Sedative H1 Antihistamines by Adults: A Cross-Sectional Investigation in France

Abstract: BackgroundGiven the growing worldwide market of non-prescription drugs, monitoring their misuse in the context of self-medication represents a particular challenge in Public Health. The aim of this study was to investigate the prevalence of misuse, abuse, and dependence on non-prescription psychoactive drugs.MethodDuring one month, in randomly solicited community pharmacies, an anonymous questionnaire was offered to adults requesting paracetamol (control group), codeine combined with paracetamol in analgesics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 25 publications
6
61
0
2
Order By: Relevance
“…The phenomenon of codeine misuse appeared closely situated within the 'blurring' of therapeutic self-medication for legitimate medical reasons (chronic pain), and misuse for iatrogenic dependence Nielsen et al 2010;Hamer et al 2013;Roussin et al 2013;Nielsen et al 2014), alongside individual difficulties in self-identifying problematic use along their own trajectory of use (Pates et al 2002;Nielsen et al 2010). Of note were the invisible and covert characteristics of dependent use, combined with social isolation over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of codeine misuse appeared closely situated within the 'blurring' of therapeutic self-medication for legitimate medical reasons (chronic pain), and misuse for iatrogenic dependence Nielsen et al 2010;Hamer et al 2013;Roussin et al 2013;Nielsen et al 2014), alongside individual difficulties in self-identifying problematic use along their own trajectory of use (Pates et al 2002;Nielsen et al 2010). Of note were the invisible and covert characteristics of dependent use, combined with social isolation over time.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of codeine misuse and dependence is difficult to monitor and quantify, and relies on indicators based on surveillance of treatment cases for codeine dependence (Pates et al 2002;Skurtveit et al 2011;Roussin et al 2013). Codeine dependence is generally treated in residential detoxification programmes, with opiate substitution therapy (methadone or buprenorphine) or lofexidine in community detoxification (Frei et al 2010;Mattick et al 2008;Kelly & Madadi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reinforcers for problematic consumption include use relating to intoxicating purposes and when benefits of misuse outweigh adverse consequences (Casati, Sedefov et al 2012). The interplay between chronic non-cancer pain, self-medication of codeine and iatrogenic dependence has also been observed (Arora, Roxburgh et al 2013;Roussin, Bouyssi et al 2013;Hamer, Spark et al 2014). Reported health consequences from long term and/or excessive misuse of combination codeine analgesics include headaches, nephrotoxicity, gastro-intestinal conditions, hypokalaemia, acute haemorrhagic and necrotizing pancreatitis (Dyer, Martin et al 2004;Dutch 2008;Ernest, Chia et al 2010;Evans, Chalmers-Watson et al 2010;Frei, Nielsen et al 2010;McDonough 2011;Pilgrim, Dobbin et al 2013;Pilgrim and Drummer 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In common with other studies, denial of having a problem was listed as the biggest barrier preventing individuals misusing or dependent on codeine from coming to treatment, followed by not being ready for change and lack of awareness of where to go for treatment. [11][12][13] Research has shown that codeine users can feel ashamed when they realise they are dependent. Many perceive themselves as respectable, professional and highly functioning, and struggle to view themselves as an 'addict' .…”
Section: Discussionmentioning
confidence: 99%